THE LEGAL BASIS OF THE STATE ANTI-CORRUPTION POLICY IN THE FIELD OF EDUCATION - Rasul A. Gusengadzhiev (Russian Studies in Law and Politics)
Relevance. Studies in different regions of the Russian Federation confirm that corruption affects all spheres of society. The education system has not been left out. This negative phenomenon is also characteristic of this department, which, in turn, should become a standard of honesty and fairness, given its main activity – education and socialization of the younger generation. Therefore, corruption in the field of education has irreparable omissions and serious consequences.